Culturally-Responsive Relational Practice at the Chalk-Face: A journey to Authenticity (Kairaranga, 2020)
This research provides chalk-face insights from a group of predominantly Pakeha teachers grappling with culturally-responsive relational practice (CRRP), in a time and environment where external factors can affect self-efficacy and limit personal agency. Itdetails a two-phased professional inquiry undertaken with fourteen teachers from one Ka hui Ako, whereby themes from a larger cross-school online survey were unpacked through a series of semi-structured focus groups. In every phase of this research, including this final telling, the emphasis was on foregrounding the stories of teachers. Findings critique taken-for-granted assumptions about teachers’ roles and responsibilities for embedding CRRP, and stress that in our efforts to stop deficising students, we do not unintentionally deficise teachers.